Inventory of terrestrial vertebrate wildlife species in a private-owned forest patch in Tagum City, Mindanao, Philippines (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Gamalo LED, Cabrera SME, Reyes NCLDL, Cadiz AED, JR Chavez JB, Raganas AFM, Quibod MANRM. 2023. Inventory of terrestrial vertebrate wildlife species in a private-owned forest patch in Tagum City, Mindanao, Philippines. Biodiversitas 24: 1104-1116. The 93-hectare Hijo Forest, owned by the Hijo Resources Corporation, is known for its rich flora and fauna species, such as the populations of long-tailed macaques (Macaca fascicularis) and Philippine warty pigs (Sus philippensis). In 2021, the Hijo management reported a mass die-off of Philippine warty pigs in the area due to the African Swine Fever (ASF) outbreak. In response to this, conservation actions and research initiatives were initiated. This includes the inventory of wildlife vertebrate fauna in the forest through day and night transect surveys, mist netting, trapping, and opportunistic sampling. A total of 12 mammals, 16 reptiles, 10 amphibians, and 67 bird species were recorded in the study. Local reports also contributed to the addition of seven taxa not recorded by the team. In total, 125 terrestrial vertebrate wildlife species inhabiting the Hijo forest were identified based on past and present fieldwork and local reports. These include species considered Critically Endangered, Endangered, Vulnerable, or Other Threatened Species, namely M. fascicularis, Carlito syrichta, Sus philippensis, Hydrosaurus pustulatus, Ophiophagus hannah, Naja samarensis, Gonyosoma oxycephalum, Malayopython reticulatus, Tropidolaemus subannulatus, Gekko intermedium, Gekko gecko, Cuora amboinensis, Varanus cumingi, Penelopides affinis, Phapitreron amethystinus, Hypothymis helenae and Loriculus philippensis. The high species richness of vertebrate fauna and the presence of numerous threatened species highlights the importance of the Hijo forest in biodiversity conservation in the region. At the same time, the presence of threats, such as the recent local extinction of Philippine warty pigs due to ASF, signals an immediate call for continuous and long-term protection of the forest. This includes collaboration with research universities, government and private institutions, and other organizations, and the need for a long-term education program to be implemented in the area.
Keywords: Beach forest, Mindanao Island, terrestrial vertebrate fauna, threatened species, wildlife